Development of phyllanthus niruri (dukung anak) chewable tablet / Meor Mohd Redzuan Meor Mohd Affandi - Meor Mohd Affandi, Meor Mohd Redzuan (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2010)
The aim of this study is to formulate Phyllanthus niruri chewable tablet and to conduct customers’ acceptance study towards the newly formulated product. The tablet was prepared by using wet granulation process and physical characterization tests were carried out by collecting a sample of tablets from the batch and determining their uniformity of weight, hardness, thickness, diameter and friability. The customer acceptance study was done by distributing questionnaires to 30 Universiti TeknologiMARA students. The results showed that the formulated Phyllanthus niruri chewable tablet was within the specification as per British Pharmacopeia and were positively accepted by the respondent. The shape and texture of the tablets significantly (P < 0.05)influenced the customers’ satisfaction towards the physical appearance of the product. In terms of taste, the customers’ satisfaction are significantly (p < 0.05) influenced by the sweetness, sourness and cola flavor of the product. In conclusion Phyllanthus niruri chewable tablet was successfully formulated with the good acceptance by the respondents.